Structural Analysis of a High Rise Building with Floating Column for long Span Structures - Prajapati, Dharmendra; Satbhaiya, Rahul (International Journal of Scientific Research in Civil Engineering, 2019)
Now a days, in India having open first story in urban multi-storey building as an unusual feature. Primarily this space is adopted for parking purpose or used for reception lobbies in first storey, at the time of earthquake total seismic base shear is experienced by a building depend on its natural period, this seismic force distribution of building is dependent on the distribution of mass and stiffness along the height of building. According to the size, shape and geometry of building, the behavior of building at the time of earthquake dependent critically, in general way to how the load is transfer to the ground. In multi-storey building the earthquake load is dependent on the height of the floors. In this floor load on the building is transfer to the ground by shortest path of the building. If there is any problem to transfer the load in shortest path; it’s shows the poor quality of building. At time of earthquake a sudden jump in vertical setback of building at the lever of discontinuity. In this study we are analyzing a multistory structure considering long span beams and floating columns.
Keywords: Floating Column; Structural Analysis; Analysis Tool; Forces; Moment; Cost; Displacement